Range‐wide breeding habitat use of the critically endangered Yellow‐breasted Bunting Emberiza aureola after population collapse. Issue 13 (18th May 2021) - Beermann, Ilka; Thomas, Alexander; Anisimov, Yury; Bastardot, Marc; Batbayar, Nyambayar; Davaasuren, Batmunkh; Gerasimov, Yury; Hasebe, Makoto; Nakul, Gleb; Nergui, Jugdernamjil; Ktitorov, Pavel; Kulikova, Olga; et al.
Abstract: The population of the Yellow‐breasted Bunting Emberiza aureola, a formerly widely distributed and abundant songbird of northern Eurasia, suffered a catastrophic decline and a strong range contraction between 1980 and 2013. There is evidence that the decline was driven by illegal trapping during migration, but potential contributions of other factors to the decline, such as land‐use change, have not yet been evaluated. Before the effects of land‐use change can be evaluated, a basic understanding of the ecological requirements of the species is needed. We therefore compared habitat use in ten remaining breeding regions across the range, from European Russia to Japan and the Russian Far East. We also assessed large‐scale variation in habitat parameters across the breeding range. We found large variation in habitat use, within and between populations. Differences were related to the cover and height of trees and shrubs at Yellow‐breasted Bunting territories. In many regions, Yellow‐breasted Buntings occupied early successional stages, including anthropogenic habitats characterized by mowing, grazing, or fire regimes. We found that the probability of presence can be best predicted with the cover of shrubs, herbs, and grasses. Highest probabilities were found at shrub cover values of 40%–70%. Differences in habitat use along a longitudinal gradient were small, but we found strong differences across latitudes, possibly related to habitat availability. We conclude that the remaining Yellow‐breasted Bunting populations are not limited to specific habitat types. Our results provide important baseline information to model the range‐wide distribution of this critically endangered species and to guide targeted conservation measures. Abstract : We compared habitat use of the critically endangered Yellow‐breasted Bunting in ten remaining breeding regions across the range and assessed large‐scale variation in habitat parameters. We conclude that the remaining Yellow‐breasted Bunting populations are not limited to specific habitat types. Our results provide important baseline information to model the range‐wide distribution of this threatened species.